Analysis of the application of good manufacturing practices (GMP) and sanitation standard operating procedures (SSOP) for products "Emping Singkong Super Telur Bu Siti" in Bantul, Yogyakarta - Alghaniya, Aliyya; Fitriani, Aprilia (Journal of Halal Science and Research, 2023)
Cassava (Manihot esculenta Crantz) is used by Mrs. Siti to be processed into cassava chips. In processing a food product, it is mandatory to implement employee sanitation and hygiene to ensure food safety. Therefore, it is necessary to evaluate the implementation of Good Manufacturing Practices (GMP) analysis based on the Regulation of the Minister of Industry of the Republic of Indonesia No. 75 of 2010 and evaluation analysis of the implementation of Sanitation Standard Operating Procedures. (SSOP) based on Head of BPOM Regulation Number HK.03.1.23.04.12.2207 of 2012 to determine the implementation of GMP and SSOP. The data collection methods used in this practical work report are observation, interviews, and literature studies. The analysis technique is by the fishbone method. The analysis results of GMP implementation show six aspects of critical (critical) deviations, including buildings, materials, final products, employees, and elimination of nuisance pests from processing units. The results of the analysis of SSOP implementation show that there are three aspects that are not in accordance with the provisions, which should include the condition and cleanliness of surfaces in contact with food ingredients, preventing cross-contamination, and eradicating nuisance pests. Based on the results of the fishbone diagram analysis, it can be concluded that there is a need for improvement in the cassava chip production process. Namely, employees are required to wash their hands before and after the production process, clean up trash around the factory, and maintain the cleanliness of raw materials, such as washing vegetables before use. So, there needs to be socialization regarding GMP and hygiene. Keywords: GMP, SSOP, Sanitation, Hygiene, Fishbone